2021
DOI: 10.1080/17437199.2021.1986417
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of loneliness and use of primary health care

Abstract: Loneliness is a growing public health concern that is associated with a range of negative health outcomes. The extent to which loneliness may also be associated with greater use of primary health care remains unclear. The present meta-analysis aimed to address this gap by quantifying research on the association of loneliness to primary health care use. The database searches yielded 23 eligible studies with 25 effects, total N = 113,639. A random effects meta-analysis revealed a small positive average effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
2
17
0
1
Order By: Relevance
“…Living alone was also related to a greater likelihood of making a specialist appointment. This fits with the findings that elderly people living alone have generally poorer physical and emotional health, compared with those living with relatives ( 17 ), and that loneliness among older populations has been shown to be related to greater use of primary care services ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 87%
“…Living alone was also related to a greater likelihood of making a specialist appointment. This fits with the findings that elderly people living alone have generally poorer physical and emotional health, compared with those living with relatives ( 17 ), and that loneliness among older populations has been shown to be related to greater use of primary care services ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 87%
“…19 26 Researchers examining loneliness and visits to primary care providers have found that those who are lonely have a greater number of visits to providers than those who are not lonely. 25 These findings may in part be due to a lonely person's desire to connect socially with care providers and integrate the provider into their social network or support system. Lonely individuals having unmet healthcare needs may also point to challenges accessing other routine or preventative services and using health services outside a reactive, acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining loneliness, health service use and unmet healthcare needs have found important sex differences 25. More older women report feeling lonely compared with older men 26 27.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Cacioppo et al, 2006;Hawkley, 2022;Holt-Lunstad et al, 2015;Kennedy et al, 1988;Seeman, 2001;Sirois & Owens, 2021) with articulated pathways for health impacts(Hawkley, 2022;Hawkley & Cacioppo, 2010), there remains opportunities to identify potential antecedents for loneliness. Writings on belongingness suggest a connection with loneliness such that a perception of being socially isolated would lead to the pain of loneliness(Baumeister & Leary, 2017…”
mentioning
confidence: 99%